Red and green loops help uncover missing feedbacks in a coral reef social–ecological system. Issue 3 (19th May 2020) - Dajka, Jan‐Claas; Woodhead, Anna J.; Norström, Albert V.; Graham, Nicholas A. J.; Riechers, Maraja; Nyström, Magnus
Abstract: Social–ecological systems (SES) exhibit complex cause‐and‐effect relationships. Capturing, interpreting, and responding to signals that indicate changes in ecosystems is key for sustainable management in SES. Breaks in this signal–response chain, when feedbacks are missing, will allow change to continue until a point when abrupt ecological surprises may occur. In these situations, societies and local ecosystems can often become uncoupled. In this paper, we demonstrate how the red loop–green loop (RL–GL) concept can be used to uncover missing feedbacks and to better understand past social–ecological dynamics. Reinstating these feedbacks in order to recouple the SES may ultimately create more sustainable systems on local scales. The RL–GL concept can uncover missing feedbacks through the characterization of SES dynamics along a spectrum of human resource dependence. Drawing on diverse qualitative and quantitative data sources, we classify SES dynamics throughout the history of Jamaican coral reefs along the RL–GL spectrum. We uncover missing feedbacks in red‐loop and red‐trap scenarios from around the year 600 until now. The Jamaican coral reef SES dynamics have moved between all four dynamic states described in the RL–GL concept: green loop, green trap, red loop and red trap. We then propose mechanisms to guide the current unsustainable red traps back to more sustainable green loops, involving mechanisms of seafood trade and ecological monitoring. By gradually moving away from seafood exports, Jamaica may be able to return to green‐loop dynamics between the local society and their locally sourced seafood. We discuss the potential benefits and drawbacks of this proposed intervention and give indications of why an export ban may insure against future missing feedbacks and could prolong the sustainability of the Jamaican coral reef ecosystem. Our approach demonstrates how the RL–GL approach can uncover missing feedbacks in a coral reef SES, a way the concept has not been used before. We advocate for how the RL–GL concept in a feedback setting can be used to synthesize various types of data and to gain an understanding of past, present and future sustainability that can be applied in diverse social–ecological settings. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.